2015
DOI: 10.1128/genomea.01419-14
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Halomonas hydrothermalis MTCC 5445, Isolated from the West Coast of India

Abstract: We announce here the draft genome sequence of Halomonas hydrothermalis MTCC 5445, a halophilic bacterium of the class Gammaproteobacteria. It was isolated from the sea coast of Aadri, Veraval, Gujarat, India. Its genome contains genes for polyhydroxybutyrate (PHB), a biodegradable polymer that can be used as a substitute for petroleum plastics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Halomonas hydrothermalis MTCC 5445 with NCBI Genbank accession no. GU938192 isolated from Aadri Veraval, Gujarat (20°57.584′ N, 70°16.659′ E) 33 has been used in current study. It was maintained in Zobell marine agar (ZMA) slants at 4 °C until use.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Halomonas hydrothermalis MTCC 5445 with NCBI Genbank accession no. GU938192 isolated from Aadri Veraval, Gujarat (20°57.584′ N, 70°16.659′ E) 33 has been used in current study. It was maintained in Zobell marine agar (ZMA) slants at 4 °C until use.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…3 ) ( Grigoriev, 1998 ). The comparative ana­lysis of gene locations between A020, Halomonas hydrothermalis ( Bharadwaj Sv et al , 2015 ), and H. meridiana ( Meyer et al , 2015 ) revealed genome translocation in each case at positions symmetric to the axes of ori and ter . Among the 3,673 protein-coding genes, 3,177 were well conserved (e value <10 –5 ) among Halomonas strains, 369 were conserved among certain Halomonas and other bacterial strains, and 127 did not exhibit similarities in databases.…”
Section: Resultsmentioning
confidence: 99%
“…3) (Grigoriev, 1998). The comparative analysis of gene locations between A020, Halomonas hydrothermalis (Bharadwaj Sv et al, 2015), and H. meridiana (Meyer et al, 2015) revealed genome translocation in each case at A) Eleven Halomonas isolates and a control strain (Halomonas sp. KM-1) were cultured on SOT agar media (2.5% NaCl, pH 9.5) supplemented with 3% sucrose at 33°C (basic conditions).…”
Section: Whole-genome Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A similar growth trend was observed at different time intervals with varying concentration which depicts the optimum time of harvesting to be 48 h and 72 h for H. daqingensis and H. ventosae respectively. Whole genome sequenced Halomonas hydrothermalis is reported to accumulate co-polymer when fed with crude levulinic acid and Jatropha biodiesel wastes ( Bera et al, 2015 ; Bharadwaj et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%